2004
DOI: 10.1111/j.1365-2591.2004.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two different calcium hydroxide combinations on root dentine microhardness

Abstract: The use of Ca(OH)2 combinations for intracanal dressing softens dentine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
(63 reference statements)
2
30
2
Order By: Relevance
“…Traditional work focusing on mechanical properties of radicular dentine after exposure to various root canal irrigants and/or medicaments has utilized Knoop or Vickers indentation techniques to measure microhardness [9][10][11]. However, there are limitations associated with the use of this regular indentation technique to determine radicular dentine microhardness.…”
Section: Manuscriptmentioning
confidence: 99%
“…Traditional work focusing on mechanical properties of radicular dentine after exposure to various root canal irrigants and/or medicaments has utilized Knoop or Vickers indentation techniques to measure microhardness [9][10][11]. However, there are limitations associated with the use of this regular indentation technique to determine radicular dentine microhardness.…”
Section: Manuscriptmentioning
confidence: 99%
“…PiezonMaster 400 (Electro Medical Systems [EMS], Richardson, TX) was the ultrasonic unit used in this experiment. Microstone (Whip Mix Corporation, Louisville, KY) was mixed according to manufacturer's instruction and 5-mm thick dental stone blocks were made and set for at least 48 h before the experiment to have the hardness similar to dentin (15,16). All ultrasonic tips were operated under minimal power setting on the dial of the ultrasonic generator.…”
Section: Methodsmentioning
confidence: 99%
“…For dentin, the hardness has been reported in the range of 52 to 64 KHN 14,19 or 46 to 53 VHN 15 . The standard deviation of hardness in this study showed a broad variation, similar to previous reports 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous microhardness studies reported results of both KHN and VHN at different indentation loads and times [4][5][6][7][8][13][14][15] . There are many reasons to perform tests at different conditions.…”
Section: Discussionmentioning
confidence: 99%